2020
DOI: 10.1088/1748-9326/ab68aa
|View full text |Cite
|
Sign up to set email alerts
|

Central Taiwan’s hydroclimate in response to land use/cover change

Abstract: Land use/cover change (LUCC) has taken place since the 1990s in central Taiwan; however, its impacts on the local and regional hydroclimatology are not understood thoroughly. This study is grounded in a numerical experiment using the Weather Research and Forecasting (WRF) model and statistical assessments of continuous land cover and gridded precipitation data derived for central Taiwan. We incorporate survey-based land use data in 1995 and 2007 in driving WRF to simulate selective non-rainy and rainy (dry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The peculiarity of this site may be linked to the presence of a protected forest in this region. The land use/land cover changes affect the local climate [32,33,88,89]. This result is in agreement with that found by Spear et al [76], who found increases in the temperature of approximately 0.4 to 1.4°C along the coasts and other areas of Western Africa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The peculiarity of this site may be linked to the presence of a protected forest in this region. The land use/land cover changes affect the local climate [32,33,88,89]. This result is in agreement with that found by Spear et al [76], who found increases in the temperature of approximately 0.4 to 1.4°C along the coasts and other areas of Western Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it should be noted that the variation of the surface temperature remains dependent on certain non-meteorological factors such as warm bias in nighttime minimum temperatures, poor siting of the instrumentation and effect of wind, as well as surface atmospheric water vapor content on temperature trends, the quantification of uncertainties in the homogenization of surface temperature data and the influence of land use/land cover changes [32]. Especially, land cover changes (LCCs) is a factor that may rapidly change local climates.…”
Section: Introductionmentioning
confidence: 99%
“…TCCIP applies sophisticated interpolation techniques to the production of gridded rainfall data for the whole Taiwan's territory at a 5-km spatial resolution and daily time step, and the currently available data range from 1960 to 2019. As still the best available gridded data, the TCCIP dataset has been applied to a number of studies (e.g., [3,16,20]). To suit our need for calculating the SPI series, we have aggregated both the gauge and TCCIP data at the daily time scale to monthly.…”
Section: Study Region and Datamentioning
confidence: 99%
“…To unravel the characteristics of climate conditions varying over time, trend analysis commonly adopted in many scientific disciplines has come into play. In the field of meteorology and climate sciences, trend analysis actually has already exhibited various applications, including the understanding of temporal patterns of hydroclimatic variables (e.g., precipitation, temperature, and streamflow) subject to climate change [2] and land use/cover change [3]. Results from trend analysis could also be incorporated in the development of climate adaptation strategies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other land-use changes, in addition to the urban effect, can similarly have effects on regional climate that are at least as large as from added GHGs (e.g., [8,[15][16][17][18][19][20][21][22][23][24][25]). Niyogi [22], for example, reported on increasing heavy rains in India with resulting alterations in hydroclimate due to changes in land use and land cover.…”
Section: Introductionmentioning
confidence: 99%